PENGUKURAN KINERJA PEGAWAI DENGAN METODE ANALYTICAL HIERARCHY PROCESS DALAM PEMBERIAN TUNJANGAN PEGAWAI DI DESA CIHERANG KECAMATAN PACET KABUPATEN CIANJUR - Eryna Syahadatina A.B Eryna Syahadatina A.B; Cecep Wahyu Hoerudin Cecep Wahyu Hoerudin; Husen Husen Saeful Anwar Anwar Husen Saeful Anwar (Sekolah Tinggi Pariwisata Mataram, 2022)
Having the quality of creative and innovative human resources (HR) becomes the focus in realizing the aims and objectives of Ciherang Village in carrying out the duties and responsibilities of employees at the village level. As a public agency that has a policy of Ciherang Village, it provides allowances in addition to the basic salary to spur the performance and work productivity of its employees. As for how to measure employee performance at the Ciherang Village Office, the Analytical Hierarchy Process (AHP) and rating scale methods are applied. The purpose of this study is to design a specific, objective, and structured employee performance measurement process and select employees who are entitled to be the main priority for additional benefits. . The research method used is descriptive with a quantitative approach. Data collection techniques for primary data are observation, interviews, and questionnaires. For secondary data obtained from literature study. The results of this study are that there are six main criteria consisting of work quality, attendance discipline, attitude, initiative, honesty and cooperation and includes 16 sub-criteria. From the results of the weighting that becomes the main priority in measuring employee performance is the work quality criterion (0.241) and in the sub-criteria there is the lowest weight, namely being able to maintain work tools (0.034) and being able to complete tasks on time (0.132) being the highest weight. And the main priority for getting additional allowances is the employee who serves as the planning department with a total score of 3,272.